2019
DOI: 10.1101/728154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative investigation into formycin A and pyrazofurin A biosynthesis reveals branch pathways for the construction ofC-nucleoside scaffolds

Abstract: 24Formycin A (FOR-A) and pyrazofurin A (PRF-A) are purine-related C-nucleoside 25 antibiotics, in which ribose and a pyrazole-derived base are linked by a C-glycosidic 26 bond, however, the logic underlying the biosynthesis of these molecules has 27 remained largely unexplored. Here, we report the discovery of the pathways for 28 FOR-A and PRF-A biosynthesis from diverse actinobacteria, and demonstrate that 29 their biosynthesis is initiated by a lysine N 6 -monooxygenase. Moreover, we show 30 that the f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Their biosynthetic gene clusters were identified recently and both clusters contain spb38/spb40/ spb39 relevant genes forK/forJ/forL and pyrM/pyrN/pyrL (also called as prfK/prfJ/prfL) indicating similar hydrazineformation pathways. 81,85,86 Previous feeding studies of pyrazomycin 86 and formycin 87 have revealed nitrogen N1 in pyrazole from the N6 of L-lysine, consistent with the occurrence of pyrM and pyrN, and C1-4 carbons are derived from L-glutamate 87 (Fig. 17A).…”
Section: Biosynthesis Of Linear Hydrazines and Pyrazolessupporting
confidence: 70%
“…Their biosynthetic gene clusters were identified recently and both clusters contain spb38/spb40/ spb39 relevant genes forK/forJ/forL and pyrM/pyrN/pyrL (also called as prfK/prfJ/prfL) indicating similar hydrazineformation pathways. 81,85,86 Previous feeding studies of pyrazomycin 86 and formycin 87 have revealed nitrogen N1 in pyrazole from the N6 of L-lysine, consistent with the occurrence of pyrM and pyrN, and C1-4 carbons are derived from L-glutamate 87 (Fig. 17A).…”
Section: Biosynthesis Of Linear Hydrazines and Pyrazolessupporting
confidence: 70%
“…To connect two nitrogen atoms together, nature has devised different strategies. The most frequently used precursors for N-N bond formation are hydroxylamines (such as L-N 5 -OH-Ornthine in piperazate pathway 9 , N-isobutylhydrdoxylamine in valanimycin pathway 37 , and L-N 6 -OH-lysine in the pathways of s56-p1 14 , pyrazomycin 16 and formycin 17,38 ) and nitric acid, which derives from the α-amine of L-aspartic acid by the enzyme pair CreE and CreD 10 . The flavin monooxygenase CreE and nitrosuccinate lyase CreD were first characterized in the cremeomycin pathway, and their homologs were subsequently identified in the pathways of fosfazinomycin, and kinamycin, triacsins and alanosine 15,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the biosynthetic origins of bioactive C-nucleosides have resulted from the identification of the gene clusters encoding a number of these secondary metabolites [19][20][21][22][23][24][25][26][27][28]. In broad terms, the cellular pathways to these natural products use three distinct chemical strategies to make the key C-C bond (electronic supplementary material, figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Reattachment of the nucleobase to the ribose via a C-C bond then follows rotation of the base within the active site [26,27]. In the third strategy, formycin A and pyrazofurin A arise from direct coupling of a small heteroaromatic dicarboxylic acid to 5 0 -phosphoribose-1 0 -pyrophosphate (PRPP) with concomitant decarboxylation [22,30].…”
Section: Introductionmentioning
confidence: 99%